Human Rights and Development - Forsythe, David P. author. aut Link
XVI, 369 p.
Keywords: This collection of papers presents an argument in support of action for human rights in the Third World, emphasizing not economic or historical determinism but rather the importance of political choice by elites in deciding which rights to violate or respect.